Urbanization and urban canals: water quality assessment of the Una hydrographic basin in Belém City, Brazil (Research, Society and Development, 2020)
The protection of urban channels becomes increasingly necessary when the levels of degradation of water resources tend to increase worldwide. This article deals with an evaluation of the water quality of the main channels (São Joaquim channel, Pirajá channel, Antônio Baena channel and Una channel) that depart from the Una hydrographic basin in the municipality of Belém, Pará State-Brazil. For the evaluation, three measurement campaigns were carried out at four points determined in the channels of the Una hydrographic basin, in the period considered mostly rainy, from April to June 2012, with the following physical-chemical parameters being surveyed: dissolved oxygen, water temperature, biochemical oxygen demand, Nitrate, pH, turbidity, Total Phosphate and fecal Coliform, for the determination of the Water Quality Index (WQI) of the channels, in addition to determining the flow of the basin using the ADCP (Acoustic Doppler Current Profiler). In general, the WQI of the main channels had a regular result, only the Antônio Baena Channel had a bad WQI. The work contributes to the management and planning of water resources in the region.